The epidemiology of alcohol use disorders cross-nationally: Findings from the World Mental Health Surveys. (March 2020) - Glantz, Meyer D.; Bharat, Chrianna; Degenhardt, Louisa; Sampson, Nancy A.; Scott, Kate M.; Lim, Carmen C.W.; Al-Hamzawi, Ali; Alonso, Jordi; Andrade, Laura Helena; Cardoso, Graca; De Girolamo, Giovanni; Gureje, Oye; et al.
Abstract: Background: Prevalences of Alcohol Use Disorders (AUDs) and Mental Health Disorders (MHDs) in many individual countries have been reported but there are few cross-national studies. The WHO World Mental Health (WMH) Survey Initiative standardizes methodological factors facilitating comparison of the prevalences and associated factors of AUDs in a large number of countries to identify differences and commonalities. Methods: Lifetime and 12-month prevalence estimates of DSM-IV AUDs, MHDs, and associations were assessed in the 29 WMH surveys using the WHO CIDI 3.0. Results: Prevalence estimates of alcohol use and AUD across countries and WHO regions varied widely. Mean lifetime prevalence of alcohol use in all countries combined was 80%, ranging from 3.8% to 97.1%. Combined average population lifetime and 12-month prevalence of AUDs were 8.6% and 2.2% respectively and 10.7% and 4.4% among non-abstainers. Of individuals with a lifetime AUD, 43.9% had at least one lifetime MHD and 17.9% of respondents with a lifetime MHD had a lifetime AUD. For most comorbidity combinations, the MHD preceded the onset of the AUD. AUD prevalence was much higher for men than women. 15% of all lifetime AUD cases developed before age 18. Higher household income and being older at time of interview, married, and more educated, were associated with a lower risk for lifetime AUD and AUD persistence. Conclusions: Prevalence of alcohol use and AUD is high overall, with large variation worldwide. The WMH surveys corroborate the wide geographic consistency of a number of well-documented clinical and epidemiological findings and patterns. Highlights: Alcohol use and alcohol use disorder (AUD) prevalence rates varied across countries. Mean lifetime prevalences were 80% for alcohol use and 8.6% for AUD. Risk of AUD onset began in adolescence, with 15% of all cases developed by age 18. Comorbidity was high, with other mental disorders most often preceding AUD onset. Patterns of AUDs and correlates were consistent across counties.